Dawson's Fingers in Cerebral Small Vessel Disease - Lv, Aowei; Zhang, Zaiqiang; Fu, Ying; Yan, Yaping; Yang, Li; Zhu, Wenli (Frontiers in Neurology, 2020)
To explore Dawson's fingers in cerebral small vessel disease (CSVD) and factors related to the development of Dawson's finger, we collected and analyzed clinical data of 65 patients with CSVD. We found a venous abnormality feature called Dawson’s fingers around the ventricles in magnetic resonance images (MRIs) of 20 out of 65 patients with CSVD (30.8%). A significant association between Dawson's fingers and diabetes mellitus (DM) was also detected (30% vs. 8.9%, P < 0.05). CSVD patients with Dawson’s fingers had significantly increased cerebral microbleeds (CMB) (44.2% vs. 75.0%, p < 0.05), lacunae (66.7% vs. 95.0%, p < 0.05), and white matter hyperintensity (WMH) (p < 0.05) damage, and these patients exhibited significant cognitive domain impairment as assessed via Montreal Cognitive Assessment (MoCA) (18.9 ± 1.8 vs. 24.0 ± 0.8, p < 0.05) and Mini-Mental State Examination (MMSE) (24.5 ± 1.1 vs. 26.6 ± 0.6, p < 0.05). Our results show a distinctly high incidence of Dawson's fingers in CSVD patients and identify a significant association with DM, thus yielding insights about the appropriate use of Dawson's fingers, a venous imaging marker, to explore the basic pathophysiology of CSVD.